"The image speaks for itself" – or does it? Instant news icons, impromptu publics, and the 2015 European "refugee crisis". Issue 4 (December 2016) - Mortensen, Mette
Easy internet access and ubiquitous smart phones have augmented the number of images produced and accelerated the speed by which they are circulated (and likely also forgotten). By contrast to the great quantity of pictures disseminated in today's connective media, a few photographs gain momentum and are declared to be "icons". They stand out from the image abundance, grasp the attention of a broad, transnational public, and stir emotional reactions and heated debates. Usually, these iconic images are related to major news events and represent an ongoing conflict or crisis in society in a simple, univocal manner. They quickly turn into standard frames of reference in news and popular culture, seem to require no particular explanation, and are often proclaimed to "speak for themselves". This article proposes the term "instant news icon" to define and gain a fuller understanding of the role performed by iconic images in today's connective media, distinguished by convergence between platforms and blurred boundaries between media production and media consumption. First, the article builds a framework based on the concept instant news icon and then applies quantitative and qualitative analyses to study the processes of distribution and meaning-making involved in the emergence of one instant news icon, news photographs from 2015 of a young refugee girl playing with a police officer on a Danish motorway.